2006
DOI: 10.1182/blood-2005-05-1875
|View full text |Cite
|
Sign up to set email alerts
|

Wegener autoantigen induces maturation of dendritic cells and licenses them for Th1 priming via the protease-activated receptor-2 pathway

Abstract: Autoantibodies to proteinase 3 (PR3) are involved in the pathogenesis of autoimmune-mediated vasculitis in Wegener granulomatosis (WG). To address the question how the autoantigen PR3 becomes a target of adaptive immunity, we investigated the effect of PR3 on immature dendritic cells (iDCs) in patients with WG, healthy blood donors, and patients with Crohn disease (CD), another granulomatous disease. PR3 induces phenotypic and functional maturation of a fraction of blood monocyte-derived iDCs. PR3-treated DCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 47 publications
1
65
0
4
Order By: Relevance
“…All 3 are diseases in which Th1 cells play a predominant role (13,14). This type of T cell also appears very important in the pathogenesis of WG (15)(16)(17)(18). More recently, it has become clear that another subset of T cells, Th17 cells, may contribute to the pathogenesis of diseases that were until now considered to be predominantly mediated by Th1 cells (19).…”
Section: Introductionmentioning
confidence: 99%
“…All 3 are diseases in which Th1 cells play a predominant role (13,14). This type of T cell also appears very important in the pathogenesis of WG (15)(16)(17)(18). More recently, it has become clear that another subset of T cells, Th17 cells, may contribute to the pathogenesis of diseases that were until now considered to be predominantly mediated by Th1 cells (19).…”
Section: Introductionmentioning
confidence: 99%
“…Activated PMN can promote DC migration (28) and also modulate DC maturation and activation through cell-cell contacts (29), ectosome release (30), or mediator secretion. Interestingly, several granule-derived mediators such as lactoferrin, LL-37, calprotectins, a-defensins, elastase, bactericidal/permeability-increasing protein, MPO, and proteinase 3 have been shown to either downregulate (31)(32)(33)(34)(35)(36)(37) or upregulate (33,(38)(39)(40)(41)) DC functions, depending on the study.…”
mentioning
confidence: 99%
“…Rarok et al found that the length of time between diagnosis and relapse was significantly shorter in WG patients with high mPR3 expression (total level of mPR3 expression), and that individuals with high total mPR3 expression were more likely to have a relapse than patients with low mPR3 (Rarok, 2002). Csernok et al showed that PR3 induces maturation of a fraction of blood monocyte derived dendritic cells (DC) in vitro (Csernok, 2006). In this context, they also observed that PR3 activates PAR-2 receptor-dependent signaling, which in turn up-regulates HLA-DR, CD80, CD83 and CD86 and down-regulates CD14.…”
Section: Pr3 and Aasvmentioning
confidence: 99%